Surgical cooperation of laparoscopic oral mucosa repair and ureteral reconstruction with robotic assistance (机器人辅助腹腔镜下口腔黏膜修复重建输尿管的手术配合) - ZHAO Yanan (赵雅楠); ZUO Jing (左静); WU Heyu (吴荷玉) (中西医结合护理)
Objective To explore the nursing cooperation process of robot-assisted laparoscopic oral mucosa repair and reconstruction of the ureter. Methods The nursing cooperation of 30 cases of robot-assisted laparoscopic oral mucosa repair and reconstruction of ureter in the Urology Department from December 2020 to December 2021 were analyzed. Intraoperative precision nursing cooperation and postoperative follow-up visits were carried outto ensure the success of surgery and safety of patients during perioperative period. Results The operation was successfully completed in 30 patients, and the overall average success rate was 95. 6%. The effect of medical and nursing cooperation was satisfactory, and no postoperative complications occurred during the short and medium-term follow-up. Conclusion Adequate preoperative preparation, reasonable operating room layout, and skilled intraoperative cooperation are considerable issues of improving the efficiency of the surgeon's operation and are an important part of the successful completion of the operation. (目的 探讨机器人辅助腹腔镜下口腔黏膜修复重建输尿管术的护理配合流程。方法 收集2020年12月—2021年12月行机器人辅助腹腔镜下口腔黏膜修复重建输尿管术治疗的30例患者的临床资料, 总结护理经验, 分析护理要点。结果 30例患者顺利完成手术, 总体平均成功率为 95. 6%。医护配合效果满意, 中短期随访无术后并发症发生。结论 充分的术前准备, 合理的手术间布局, 熟练的术中配合, 有助于能提高术者手术效率, 是确保手术顺利完成的重要环节。)